PENGAKUAN PENDAPATAN DAN BEBAN PADA PT.PRUDENTIAL LIFE ASSURANCE SAMARINDA - Sesi, Erza (EKONOMIA, 2013)
Â EZRA SESI, Revenue and Expense Recognition in PT.Prudential Life Assurance, under the guidance of Ms.Elfreda A.Lau as the first advisor and Ms. Mardiana as the second advisor.The objective of this study is to determine the recognition of premium revenue and claims expense PT.Prudential Life AssuranceCompany In Accordance With PSAK No. 36.The results showed that PT.Prudential Life Assurance adheres to the principles of revenue recognition is fundamentally in accordance with PSAK No. 36, where revenues are recognized when realization, and for the measurement of income, although not described in detail in IAS 36, as this is considered to be the things that are general or things that are not addressed in SFAS No. 36, so it is treated with reference to generally accepted accounting principles. Unlike the case with revenue recognition, PT.Prudential Life Assurance adheres to the principle of recognition of expenses that are not in accordance with PSAK No. 36, which the company expenses are recognized when incurred redemption premiums receivable, and for the measurement of the load, is also not explicitly described in SAK 36, because it is regarded as the general thing or things that are not addressed in PSAK No. 36, so that is treated with reference to generally accepted accounting principles.Based on the analysis and discussion above it can be seen that PT.Prudential Life Assurance has not been fully implemented PSAK 36 in recognition of the life insurance expenses and the preparation of the Income Statement. It can be concluded that the hypothesis has been put forward in the previous chapter on the decline.Â